Digital microwave communication systems : with selected topics in mobile communications - Sreekanth, P.V. ([S.l.] : Orient Blackswan, 2003)
This book provides a hands-on approach to Digital Microwave Communications. Students of Communications Engineering often find a wide gap between the theory they have learned and the skills required for the implementation of the communications system. The book provides the necessary theoretical inputs for understanding the basic concepts (keeping mathematical analysis to a minimum), and follows it up with the practical details of the systems and their interfaces.